Novel indole-guanidine hybrids as potential anticancer agents: Design, synthesis and biological evaluation. (1st December 2022) - Li, Jing; Si, Ru; Zhang, Qingqing; Li, Yanchen; Zhang, Jie; Shan, Yuanyuan
Abstract: Based on the scaffold hybridization strategy, twenty-four indole-guanidines were designed and synthesized. Subsequently, anti-proliferative activity against various cancer cells indicated that most of these hybrids exhibited moderate to high anti-proliferative activity, especially for human hepatoma cell lines. Selectivity investigation showed that these hybrids showed the best selectivity for SMMC-7721 subtype in human hepatoma cells. Particularly, ( E )-3-((2-( N -pentylcarbamimidoyl)hydrazono)methyl)-1 H -indol-5-yl 4-methylbenzoate (19 ) and ( E )-3-((2-( N -pentylcarbamimidoyl)hydrazono)methyl)-1 H -indol-5-yl 4-methoxybenzoate (22 ) exhibited potent inhibition against SMMC-7721 cells with IC50 values of 0.057 μM and 0.042 μM, respectively, far outperforming that of Sorafenib. Meanwhile, hybrids 19 and 22 exhibited no significant cytotoxicity against normal cells such as HEK293 cells and HEK293T cells. Moreover, further investigations indicated that hybrid 22 effectively induced apoptosis, arrested the cell cycle at S phase, and selectively down regulated expression of p-STAT3, JAK2 and BRAF in SMMC-7721 cells in a dose-dependent manner. Molecular docking indicated that hybrid 22 exhibited high affinity with STAT3 and BRAF. In summary, hybrid 22 was developed as a potential and effective anti-hepatoma candidate, which was worthy of further investigation. Graphical abstract: Discovery of several indole-guanidine hybrids as novel anti-cancer agents with novel scaffold. Image 1 Highlights: Discovery of indole-guanidine hybrids as novel and potent anti-cancer candidates with novel scaffold. Two hybrids exhibited potent and selective anti-proliferative activities with no significant cytotoxicity. The candidate 22 could induce apoptosis, arrest the cell cycle, down regulate p-STAT3, JAK2 and BRAF. In silico study indicated that the candidate 22 showed high affinity with STAT3 and BRAF.